2012
DOI: 10.1055/s-0032-1310061
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity focused ultrasound liver destruction through the gastric wall under endoscopic ultrasound control: first experience in living pigs

Abstract: High-intensity focused ultrasound liver destruction through the gastric wall under endoscopic ultrasound control: first experience in living pigs High-intensity focused ultrasound (HIFU) was first developed to ablate prostatic tissue [1]. The ultrasound beam is focused at the focal point of the transducer and the energy concentration produces tissue necrosis [2]. HIFU has also been used to ablate metastases on the surface of the liver either surgically or via the transcutaneous approach [3,4]. However, beam re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…The performance in “liver” and “pancreas” can also be generalized as possible in other similar target tissues. Some comparisons can be drawn between the simulations of the proposed applicator assemblies and experimental evaluations of ultrasound applicators developed for endoluminal ablation of liver or pancreatic tissue, as described in literature . Collectively, these applicators had ~12 mm profiles, were placed in the stomach in in vivo porcine studies, and could create thermal lesions of ~1–2 cm maximum penetration into the target liver/pancreatic tissue .…”
Section: Discussionmentioning
confidence: 99%
“…The performance in “liver” and “pancreas” can also be generalized as possible in other similar target tissues. Some comparisons can be drawn between the simulations of the proposed applicator assemblies and experimental evaluations of ultrasound applicators developed for endoluminal ablation of liver or pancreatic tissue, as described in literature . Collectively, these applicators had ~12 mm profiles, were placed in the stomach in in vivo porcine studies, and could create thermal lesions of ~1–2 cm maximum penetration into the target liver/pancreatic tissue .…”
Section: Discussionmentioning
confidence: 99%
“…Simulation and preliminary studies have been reported for phased array devices for such applicators [67-72]. Some of these designs also have integrated MR imaging coils [60, 61] or ultrasound imaging probes [62, 63]. …”
Section: Endoluminal Cbusmentioning
confidence: 99%
“…A 4-patient pilot study is reported for the ablation of tumors in the esophagus with a transesophageal applicator and feasibility of creating highly-demarcated ablative lesions in the esophagus was indicated [59]. Liver ablation using transgastric ultrasound was also demonstrated in vivo in swine models using an endoscopic device, and it was possible to create small lesions in the liver [58, 62]. Intraductal ablation of tumors in the digestive tract and billiary duct has been studied in swine models where small diameter devices (3.8 – 4 mm) have been deployed within working channels of endoscopes [84, 85].…”
Section: Endoluminal Cbusmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been long acknowledged that an endoscopic device that would integrate a HIFU transducer and an endoscopic ultrasound (EUS) imaging probe would be a safer and more efficient alternative to extracorporeal HIFU in the ablation of peri-luminal lesions 1,15 . Such an EUS-guided HIFU device would bring many potential benefits including improved targeting, decreased energy requirements, and decreased potential for injury to intervening structures.…”
Section: Introductionmentioning
confidence: 99%